Solit Upaya Mengoptimalkan Peran Guru Dalam Mengenalkan Literasi Pada Anak Usia Dini : - - Melyana Indiarsih; Kurniasih, Imas (IKIP Siliwangi Bandung, 2025)
Literacy is a programme initiated by the government as an effort to develop children's interest in literacy, including types of reading literacy. This was initiated partly because based on PISA data shows that the reading ability of Indonesian children is still relatively low. This is in line with conditions in the field where the implementation of literacy starting from facilities to other literacy support stimuli is still not appropriate and optimal, therefore socialization of literacy was held for teachers to maximise their role in providing facilities and providing stimulus for children to literate. This socialization was delivered to PAUD teachers in Bongas Village Cililin as well as the subject of this research, where literacy is expected to start early as a habit and initial foundation in order to form a generation that will love to read. The research method used was descriptive quantitative using a questionnaire instrument. The results show that teachers' understanding of literacy implementation has increased and it is hoped that with increased understanding teachers can optimize their role in increasing children's motivation to be active in literacy from an early age.